The effects of strength and conditioning interventions on golf performance: A systematic review - Ehlert, A. (Journal of Sports Sciences, 2020)
There is a growing body of literature on strength and conditioning (S&C) interventions for golfers of various skill levels. The aim of this systematic review was to evaluate the effects of S&C interventions on measures of golf performance (clubhead speed, ball speed, distance, etc.). Three databases (PubMed, SPORTDiscus, Web of Science) were searched and twenty-five studies identified that evaluated the effects of a S&C intervention on at least one golf performance measure compared to a control or comparison group. Most studies used combinations of strength training, plyometrics, stretching or core exercise, with many finding a benefit. Though it varied across studies and outcomes, average increases in clubhead speed, ball speed and distance measures were 4-6.4% when significant findings were synthesized. Four studies also found significant changes to golf swing kinematics, while three others found positive effects on measures of accuracy or consistency. Future research should compare different S&C interventions, explore the role of training status, skill level and intervention duration on the effects of S&C interventions, and report individual responses in addition to group data. Further, research should continue to evaluate effects on swing kinematics, accuracy and direct golf performance measures (e.g., handicap index).